2011
DOI: 10.1038/nmat3120
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic frustration and the nature of the magnetic and paramagnetic states in iron pnictides and iron chalcogenides

Abstract: The iron pnictide and chalcogenide compounds are a subject of intensive investigations due to their high temperature superconductivity.[1] They all share the same structure, but there is significant variation in their physical properties, such as magnetic ordered moments, effective masses, superconducting gaps and T c . Many theoretical techniques have been applied to individual compounds but no consistent description of the trends is available [2]. We carry out a comparative theoretical study of a large numbe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

114
959
4
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 819 publications
(1,082 citation statements)
references
References 31 publications
114
959
4
5
Order By: Relevance
“…These behaviors are quite consistent with the previous eDMFT calculation in iron-based superconductors [65][66][67][68][69]. We also show the mass enhancement extracted from angle-resolved photoemission spectroscopy (ARPES) experiments [19,20].…”
Section: Hypothetical Srfeas2 and Bafeas2 Compoundssupporting
confidence: 90%
“…These behaviors are quite consistent with the previous eDMFT calculation in iron-based superconductors [65][66][67][68][69]. We also show the mass enhancement extracted from angle-resolved photoemission spectroscopy (ARPES) experiments [19,20].…”
Section: Hypothetical Srfeas2 and Bafeas2 Compoundssupporting
confidence: 90%
“…By comparing results with Ref. [21], we found that among other t 2g orbitals, d xy shows the strongest temperature dependence in Z A at P=0GPa.…”
mentioning
confidence: 57%
“…Substitution of Se for Te in FeTe leads to an increase in the Se/Te -Fe -Se/Te bond angle (α shown in fig 1 (a)). The angle α which is 95 • in case of FeTe, approaches the ideal tetrahedron value of 109.5 • with Se doping [23]. The bond angle is determinant to the overlap between the iron and chalcogen orbitals, resulting in a stronger hybridization between the Fe 3d and the chalcogen p orbitals.…”
Section: Resultsmentioning
confidence: 89%